Cotton miR393-TIR1 Module Regulates Plant Defense Against Verticillium dahliae via Auxin Perception and Signaling - Shi, Gege; Wang, Saisai; Wang, Peng; Zhan, Jingjing; Tang, Ye; Zhao, Ge; Li, Fuguang; Ge, Xiaoyang; Wu, Jiahe (Frontiers in Plant Science, 2022)
Plant auxin is essential in plant growth and development. However, the molecular mechanisms of auxin involvement in plant immunity are unclear. Here, we addressed the function of the cotton (Gossypium hirsutum) miR393-TIR1 module in plant defense against Verticillium dahliae infection via auxin perception and signaling. GhTIR1 was directedly cleaved by ghr-miR393 according to mRNA degradome data, 5′-RACE analysis, and a GUS reporter assay. ghr-miR393 knockdown significantly increased plant susceptibility to V. dahliae compared to the control, while ghr-miR393 overexpression and GhTIR1 knockdown significantly increased plant resistance. External IAA application significantly enhanced susceptibility to V. dahliae in ghr-miR393 knockdown and control plants compared to mock treatment, and only slightly increased susceptibility in overexpressing ghr-miR393 and GhTIR1-silenced plants. Application of external PEO-IAA (an auxin antagonist) had a contrary trend with IAA application. Based on yeast two-hybrid and bimolecular fluorescence complementation assays, GhTIR1 interacted with GhIAA14 in the nucleus, and its knockdown reduced plant resistance to V. dahliae infection. The results suggested that the ghr-miR393-GhTIR1 module mediates plant defense via auxin perception and signaling. Additionally, simultaneous knockdown of GhTIR1 and GhICS1 significantly increased plant susceptibility to V. dahliae compared to the control, indicating that salicylic acid (SA) accumulation is vital for the ghr-miR393-GhTIR1 module to mediate plant resistance. Transcriptome data also demonstrated that GhTIR1 knockdown significantly downregulated expression of auxin-related genes and upregulated expression of SA-related genes. Overall, the ghr-miR393-GhTIR1 module participates in plant response to V. dahliae infection via IAA perception and signaling depending on the SA defense pathway.